Metaheuristic based solution approaches for the obstacle neutralization problem - ALKAYA, ALİ FUAT (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The problem of finding shortest path under certain constraints is NP-Complete except for some trivial variants. In this study, we develop metaheuristics for the obstacle neutralization problem (ONP) which is a path planning problem where the goal is to safely and swiftly navigate an agent from a given source location to a destination through an arrangement of potential mine or threat discs in the plane. To solve the ONP, ant system, genetic algorithm, simulated annealing and migrating birds optimization algorithms are developed and customized. We provide computational experiments both on real-world and synthetic data to empirically assess their performance. The results of the algorithms are compared with exact solutions on small instances. The comparison results present that our algorithms finds near-optimal solutions in reasonable execution times. Furthermore, the results show that the proposed versions of the aforementioned algorithms can be applicable to similar problems. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Path planning; Obstacle neutralization problem; Optimization; Metaheuristics; OPTIMIZATION; ALGORITHM; PERFORMANCE; AIRCRAFT